Ceramic-metal composite grinding block for coarse grinding of microcrystalline glass

By using ceramic-metal composite grinding blocks in microcrystalline glass coarse grinding, combining the characteristics of ceramic and metal diamond blocks, the problems of sharpness and service life of the grinding blocks are solved, and high-efficiency and low-cost grinding of microcrystalline glass are achieved. The process ensures the flatness and long life of the board.

CN119304795APending Publication Date: 2025-01-14HENAN UNION ABRASIVES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411432041.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing grinding blocks cannot take into account both the sharpness and service life when grinding the crystallized glass, resulting in high processing costs and low pass rate.

Method used

Using ceramic-metal composite grinding blocks, by installing multiple ceramic diamond joints and metal diamond joints on the substrate, the arrangement method, volume ratio and formula composition of the two are regulated, and the thermal stability and metal of the ceramic bonding agent are utilized. The strength of the bonding agent and the characteristics of the bonding agent achieve both grinding accuracy and sharpness.

Benefits of technology

It has achieved that the processing depth can reach more than 5mm in the rough grinding process of microcrystalline glass, the plate surface is flat and has no deep scratches, and the service life is 11,000 cubic meters, meeting the process requirements of microcrystalline glass and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304795A_ABST
    Figure CN119304795A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of grinding materials and grinding tools, and particularly relates to a ceramic-metal composite grinding block for coarse grinding of microcrystalline glass. The ceramic-metal composite grinding block for coarse grinding of the microcrystalline glass comprises a base body, ceramic diamond segment rows and metal diamond segment rows are alternately arranged in the length direction of the base body, and the grinding area ratio of all ceramic diamond segments to all metal diamond segments is (1-2.5): 1. The ceramic diamond segment is prepared from a ceramic bond, diamond, a pore forming agent, green silicon carbide powder and a wetting agent, and the metal diamond block is prepared from metal powder, graphite powder and diamond. The advantages of the two segments are utilized, the arrangement mode of the two segments, the grinding area proportion and the formula composition of the two segments are regulated and controlled, the combined action enables the composite grinding block to have the service life and the sharpness, the grinding surface of the microcrystalline glass is free of scratches, and the process requirements of the microcrystalline glass can be efficiently met with low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of abrasive materials and grinding tools, and in particular to a ceramic-metal composite grinding block for rough grinding of microcrystalline glass. Background Art

[0002] Microcrystalline stone, also known as microcrystalline glass, is a new type of high-end decorative material. It is made of natural inorganic materials through a specific process and sintered at high temperature. It has excellent characteristics such as no radiation, no water absorption, no corrosion, no oxidation, no fading, no color difference, no deformation, high strength, and high gloss. Microcrystalline stone is selected from several main components of granite and a special crystal phase is precipitated from a glass liquid with special components at high temperature. Therefore, it has high hardness and strength. During the molding process, it undergoes secondary high-temperature melting and shaping. Therefore, it does not have the texture formed by natural stone. Therefore, it is not easy to break, does not absorb water, is not afraid of erosion and pollution, and has high gloss. After decoration, there will be no color difference, alkali, spitting, etc. No maintenance is required, and it does not contain any radioactive elements in natural stone. Now more and more high-end decorations use microcrystalline glass.

[0003] At present, the following process is adopted for processing large-sized microcrystalline glass (such as 2000mm*1600mm*20mm): production of blank plate → thinning by disc thickness machine / claw thickness machine → rough grinding by polishing machine → medium grinding by polishing machine → fine grinding by polishing machine → edge grinding by edge grinding machine → packaging and subpackaging. Among them, the rough grinding process is to remove the scratches produced by the previous thinning process, and it has a certain cutting force to ensure the removal amount of the rough grinding process and meet the requirements of size thickness. In addition, the rough grinding process cannot produce new scratches, laying the foundation for the subsequent medium grinding and fine grinding. Therefore, the quality of the rough grinding process is crucial.

[0004] However, due to the following characteristics of microcrystalline glass: 1) The Mohs hardness of the crystal jade layer on the surface of microcrystalline stone is high and difficult to process; 2) The surface glossiness of microcrystalline stone is high, which can reach 80-120, and scratches will be easily visible; 3) There are a certain number of pinholes on the surface of microcrystalline stone, which are also easily visible when encountering impurities. Therefore, the cost of processing microcrystalline glass is high, and the qualified rate is not high.

[0005] At present, the rough grinding process generally uses metal diamond grinding blocks or resin diamond grinding blocks. Since metal binders and resin binders cannot produce large-pore or multi-porous matrixes, during use, microcrystalline glass powder is easy to cause grinding wheel blockage, reduced sharpness, and burn the plate. The existing solution is to adjust the grinding block structure, reduce the contact area between the grinding block and the plate, greatly improve the sharpness of the grinding block, add cooling materials such as graphite, add water-soluble powder, etc. However, this will sharply reduce the life of the grinding block, thereby increasing the production cost of microcrystalline glass. Summary of the invention

[0006] The invention provides a ceramic-metal composite grinding block for rough grinding of microcrystalline glass, which solves the problem that the existing grinding blocks cannot take into account both the sharpness and the service life of the grinding blocks when rough grinding microcrystalline glass.

[0007] In order to solve the above technical problems, the technical solution of the ceramic-metal composite grinding block for rough grinding of microcrystalline glass of the present invention is: A ceramic-metal composite grinding block for rough grinding of microcrystalline glass comprises a substrate, wherein a plurality of ceramic diamond segments and a plurality of metal diamond segments are arranged on the substrate, and the grinding area ratio of all the ceramic diamond segments to all the metal diamond segments is (1-2.5):1; the ceramic diamond segments are made of 30-50% by mass of a ceramic binder, 20-30% by mass of diamond, 10-30% by mass of a pore former, 10-30% by mass of a green silicon carbide powder, and 2-5% by mass of a wetting agent; the metal diamond segments are made of 30-60% by mass of a FeCu20-50 alloy powder, 10-35% by mass of a copper powder, 10-30% by mass of an iron powder, 2-15% by mass of a phosphorus iron powder, 2-5% by mass of a cobalt powder, 2-5% by mass of a manganese powder, 3-10% by mass of a graphite powder, and 2-5% by mass of a diamond; A plurality of ceramic diamond segments and a plurality of metal diamond segments are arranged in a plurality of rows in the length direction of the substrate, and the ceramic diamond segment rows and the metal diamond segment rows are arranged alternately in the length direction of the substrate.

[0008] The present invention is an improvement on the prior art, and provides a ceramic-metal composite grinding block for rough grinding of microcrystalline glass. The present invention provides a plurality of ceramic diamond segments and a plurality of metal diamond segments on a substrate, and regulates the arrangement mode, volume proportion and formula composition of the two segments. The ceramic diamond segments have good thermal stability and abrasive holding degree, and have a long service life. The ceramic diamond segments have multiple pores for grinding chips and storing coolant, small grinding stress, high elastic modulus, good rigidity, small elastic deformation during the grinding process, and can achieve high grinding accuracy. The segments are easy to break and thresh during the grinding process, and new cutting edges are constantly generated, so that the segments can maintain a sharp state and have high grinding efficiency. The metal binder has high strength, wear resistance, good working surface geometry, long service life, impact resistance, and can withstand heavy load grinding, but poor self-sharpening and low efficiency. The characteristics of the two segments are combined to take into account both service life and sharpness while meeting the process requirements of microcrystalline glass, so that the prepared ceramic-metal composite grinding block can grind microcrystalline glass plates (for example, 2100mm long and 1800mm wide) with high grinding efficiency. *20mm thick), the processing depth can reach more than 5mm in the rough grinding process, and the board surface is flat without deep scratches, and the service life can reach more than 11,000 square meters.

[0009] The particle size of the diamond is 45 / 50~70 / 80; the particle size of the green silicon carbide powder is one size smaller than that of the diamond; the pore-forming agent is selected from resin particles or nutshell powder, and the resin particles are selected from PMMA particles or PS resin balls; the particle size of the pore-forming agent is 30μm~100μm; the wetting agent is selected from one or more of resin liquid, water glass, dextrin liquid, and liquid paraffin.

[0010] In order to further improve the life of the grinding block and adapt to different cutting sample flatness, preferably, the shape of the ceramic diamond segment is a cylinder, and the shape of the metal diamond segment is a cuboid; the angle between the length direction of the cuboid and the length direction of the substrate is 0°~45°. The ceramic diamond segment is designed as a cylindrical structure mainly because the ceramic binder is brittle. If it is designed as a rectangular or angular shape, it will make circular motion when used on a polishing machine, and it is easy to break when processing hard and brittle materials, thereby causing grinding defects on the surface of the workpiece. Therefore, it is designed as a cylindrical structure to avoid its sharp corners from breaking during operation; when the angle is 0°, its processing area is larger during operation, and the cutting amount is larger. When the flatness of the board surface is better, a 90° structure can be used, and when the angle is 45°, it is more conducive to chip removal. When the flatness of the board surface is poor, a 45° structure is used.

[0011] In order to further improve the sharpness and service life of the grinding block, preferably, the metal diamond segment is made of 30-35% FeCu20-50 alloy powder, 30-35% copper powder, 10-15% iron powder, 5-7% ferrophosphorus powder, 2-3% cobalt powder, 2-2.5% manganese powder, 4.5-5% graphite powder and 4-4.5% diamond by mass fraction. The particle size of the graphite powder is 30#-100#, and the particle size of the diamond is 45 / 50-70 / 80.

[0012] In order to further improve the life, strength and wear resistance of the grinding block, preferably, the metal diamond segment is made by mixing various raw materials and then pressing them into shape.

[0013] In order to further improve the bonding ability of each powder of the metal diamond segment, preferably, the pressing molding is hot pressing molding, the temperature of the hot pressing molding is 600~700°C, the time of the hot pressing molding is 3~10min, and the pressure of the hot pressing molding is 50~60KN.

[0014] In order to further improve the grinding surface quality of microcrystalline glass, preferably, the ceramic diamond segment is made by mixing various raw materials and then molding and sintering them.

[0015] In order to further improve the holding degree of the ceramic binder on the abrasive and improve the grinding accuracy, preferably, the preparation method of the ceramic binder includes the following steps: 30-60% by mass of silicon dioxide, 10-30% by mass of aluminum oxide, 10-30% by mass of boric acid, 5-15% by mass of zinc oxide, 5-15% by mass of lithium carbonate and 5-20% by mass of calcium carbonate are mixed and then smelted, water quenched and crushed. The ceramic binder is obtained by sieving through a 150-200 mesh sieve after crushing. The purity of the silicon dioxide is 98%-99%; the purity of the aluminum oxide is not less than 98.5%; the purity of the zinc oxide is 95%-96%; the purity of the calcium carbonate is not less than 98.5%.

[0016] In order to further improve the sintering performance of the ceramic diamond segment, preferably, the sintering is performed by stepwise heating from 30-50°C to 700-800°C and then keeping the temperature for 100-150 minutes.

[0017] Before sintering, the molding material is placed in a 100-120°C oven for drying for 2-3 hours to remove moisture; in order to further remove moisture from the molding material and perform pore formation, preferably, the stepwise heating is: heating from 30-50°C to 100-150°C at a heating rate of 1-1.5°C / min, keeping at 100-150°C for 80-100min, then heating from 100-150°C to 400-450°C at a heating rate of 2.5-3°C / min, keeping at 400-450°C for 180-200min, and then heating from 400-450°C to 700-800°C at a heating rate of 0.5-1°C / min. The purpose of keeping the temperature at 100-150°C for 80-100 minutes is to remove moisture from the molding material, and the purpose of keeping the temperature at 400-450°C for 180-200 minutes is to decompose and discharge the pore-forming agent.

[0018] In order to further improve the bonding performance of the ceramic binder, preferably, the smelting temperature is 1200~1400°C and the smelting time is 100~200min. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic structural diagram of a ceramic-metal composite grinding block according to Example 1 of the present invention; Figure 2 For Figure 1 Schematic diagram of the structure of ceramic-metal composite grinding blocks with different arrangements; Figure 3 It is a schematic diagram of the ceramic-metal composite grinding block of the present invention being installed on a grinding disc; Figure 4 It is a schematic diagram of the structure of a conventional metal bond diamond grinding block; Figure 5It is a schematic diagram of the structure of a conventional resin bond diamond grinding block; Figure 6 This is a schematic diagram of the structure of a conventional one-piece metal bond diamond grinding block. DETAILED DESCRIPTION

[0020] The technical concept of the ceramic-metal composite grinding block for rough grinding of microcrystalline glass of the present invention is as follows: The ceramic-metal composite abrasive block provided by the present invention utilizes the respective advantages of the ceramic diamond segments and the metal diamond segments, and by regulating the arrangement mode, volume proportion and respective formula composition of the two segments, the composite abrasive block can take into account both life and sharpness, and can maintain its surface quality in the microcrystalline glass rough grinding process without scratches on the surface, and can meet the process requirements of microcrystalline glass at low cost and high efficiency.

[0021] The following is a further description of the embodiments of the present invention in conjunction with specific examples. The raw materials, equipment, etc. used in the following examples can be obtained by purchase unless otherwise specified.

[0022] 1. Specific embodiments of the ceramic-metal composite grinding block for rough grinding of microcrystalline glass of the present invention Example 1 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this embodiment is as follows: Figure 1 As shown, it includes a substrate (170 mm long and 60 mm wide), on which 18 ceramic diamond segments and 15 metal diamond segments are arranged, the ceramic diamond segments are in the shape of a cylinder, and the metal diamond segments are in the shape of a cuboid; the diameter of the ceramic diamond segment is 12 mm and the height is 12 mm; the length of the metal diamond segment is 14 mm, the width is 7 mm, and the height is 12 mm; the grinding area ratio of all ceramic diamond segments and all metal diamond segments is 1.38:1.

[0023] Multiple ceramic diamond segments and multiple metal diamond segments are arranged in multiple rows along the length direction of the substrate, and the ceramic diamond segment rows and metal diamond segment rows are arranged alternately along the length direction of the substrate; the angle between the length direction of the cuboid and the length direction of the substrate is 0°.

[0024] 1) The preparation method of metal diamond segments is as follows: 40% FeCu20 alloy powder, 20% copper powder, 20% iron powder, 7% ferrophosphorus powder, 3% cobalt powder, 3% manganese powder and 4% graphite powder with a mass fraction are put into a three-dimensional mixer and mixed for 60 minutes, and then 3% diamond and 1.5% liquid paraffin of metal diamond segment powder are added. After mixing for another 90 minutes, the mixture is poured into a graphite mold and pressed into shape using a hot press. The pressing and molding conditions are as follows: the hot press starts at a starting temperature of 80°C and a starting pressure of 15KN, gradually raises the temperature to 680°C and the pressure to 55KN, and keeps warm for 4 minutes. After completion, the burrs are removed to obtain metal diamond segments.

[0025] 2) The preparation method of ceramic diamond segments is as follows: (1) Preparation of ceramic binder 40% by mass of silicon dioxide, 20% by mass of aluminum oxide, 15% by mass of boric acid, 5% by mass of zinc oxide, 10% by mass of lithium carbonate and 10% by mass of calcium carbonate are mixed to obtain a mixture, which is then placed in a smelting furnace and smelted at 1250°C for 150 min, and then subjected to water quenching, drying, crushing and screening (150# sieve) to obtain a ceramic binder.

[0026] (2) Preparation of ceramic diamond segments 30% by mass of the ceramic binder obtained in step (1), 20% of diamond, 27% of pore-forming agent, 20% of green silicon carbide powder and 3% of wetting agent were put into a mixer and mixed for 60 minutes. After being taken out, they were put into a cold pressing mold and cold pressed at a pressure of 60 MPa to obtain a cold pressed embryo. Then, they were put into an oven and dried at 120°C for 2 hours to remove moisture. After that, they were put into a sintering furnace and sintered according to the stepwise heating in Table 1. The purpose of keeping the temperature at 100°C for 80 minutes was to continue to remove some moisture in the cold pressed embryo. The purpose of keeping the temperature at 400°C for 180 minutes was to decompose and discharge the pore-forming agent, thereby obtaining a ceramic diamond segment.

[0027] Table 1 Temperature-timetable for sintering by step-by-step heating The ceramic diamond segments prepared above are bonded to the substrate, and the metal diamond segments are welded to the substrate to obtain a ceramic-metal composite grinding block.

[0028] In this embodiment, when the angle between the length direction of the cuboid and the length direction of the base is 0°, the processing area is larger and the cutting amount is larger when grinding the workpiece.

[0029] In other embodiments, the angle between the length direction of the cuboid and the length direction of the substrate can be 45°, and the obtained ceramic-metal composite grinding block is as follows: Figure 2 As shown, it is more conducive to chip removal at this time.

[0030] When grinding the workpiece, the ceramic-metal composite grinding block can be welded to the clamping plate of the grinding disc. One grinding disc can weld 6 ceramic-metal composite grinding blocks (such as Figure 3 as shown).

[0031] Example 2 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this embodiment is basically the same as that in Example 1, except that: in step 1), 35% FeCu20 alloy powder, 34% copper powder, 10% iron powder, 7% ferrophosphorus powder, 3% cobalt powder, 2% manganese powder, and 5% graphite powder with a mass fraction are put into a three-dimensional mixer and mixed for 60 minutes, and then 4% diamond and 1.5% liquid paraffin of metal diamond segment powder are added, and after mixing for another 90 minutes, the metal diamond segment is obtained by hot pressing.

[0032] In step 2) (1), 51% by mass of silicon dioxide, 10% by mass of aluminum oxide, 18% by mass of boric acid, 8% by mass of zinc oxide, 8% by mass of lithium carbonate and 5% by mass of calcium carbonate are mixed to obtain a mixture, and the mixture is smelted, water quenched, dried, crushed and sieved (150# sieve) to obtain a ceramic binder.

[0033] In step 2), (2) 40% by mass of the ceramic binder obtained in (1), 25% of diamond, 22% of a pore former, 10% of green silicon carbide powder and 3% of a wetting agent are put into a mixer and mixed for 60 minutes. The mixture is cold pressed, dried and sintered to obtain a ceramic diamond segment.

[0034] Example 3 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this embodiment is basically the same as that in Example 1, except that: in step 1), 50% FeCu20 alloy powder, 10% copper powder, 10% iron powder, 10% ferrophosphorus powder, 2% cobalt powder, 5% manganese powder, and 8% graphite powder with a mass fraction are put into a three-dimensional mixer and mixed for 60 minutes, and then 5% diamond and 1.5% liquid paraffin of metal diamond segment powder are added, and after mixing for another 90 minutes, the metal diamond segment is obtained by hot pressing.

[0035] In step 2) (1), 30% by mass of silicon dioxide, 15% by mass of aluminum oxide, 25% by mass of boric acid, 12% by mass of zinc oxide, 5% by mass of lithium carbonate and 13% by mass of calcium carbonate are mixed to obtain a mixture, and the mixture is smelted, water quenched, dried, crushed and sieved (150# sieve) to obtain a ceramic binder.

[0036] In step 2), (2) 48% by mass of the ceramic binder obtained in (1), 30% of diamond, 10% of a pore former, 10% of green silicon carbide powder and 2% of a wetting agent are put into a mixer and mixed for 60 minutes. The mixture is cold pressed, dried and sintered to obtain a ceramic diamond segment.

[0037] The raw material ratios in the preparation process of the ceramic diamond segments and metal diamond segments of Examples 1-3 are shown in Table 2.

[0038] Table 2 Ratio of raw materials in Examples 1-3 Among them, the diamond is selected with a particle size of 45 / 50 to 70 / 80; the pore-forming agent is PMMA spherical particles with a size of 80μm; the graphite powder is selected with a particle size of 60#; the green silicon carbide powder is selected with a particle size finer than the diamond used; and the wetting agent is liquid paraffin.

[0039] 2. Comparison Comparative Example 1 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this comparative example is basically the same as that in Example 2, except that no graphite powder is added in step 1).

[0040] Comparative Example 2 The ceramic-metal composite grinding block used for rough grinding of microcrystalline glass in this comparative example is basically the same as that in Example 2, except that no pore-forming agent is added in (2) of step 2).

[0041] Comparative Example 3 The ceramic-metal composite grinding block used for rough grinding of microcrystalline glass in this comparative example is basically the same as that in Example 2, except that: no copper powder is added in step 1).

[0042] Comparative Example 4 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this comparative example is basically the same as that in Example 2, except that in step 2) (2), the green silicon carbide powder is replaced with black silicon carbide powder.

[0043] Comparative Example 5 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this comparative example is basically the same as that in Example 2, except that in step 1), the FeCu20 alloy powder is replaced with FeCu10 alloy powder.

[0044] Comparative Example 6 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this comparative example is a conventional metal bond diamond grinding block for rough grinding of microcrystalline stone, such as Figure 4As shown, it includes a substrate and a plurality of metal bond diamond segments welded in a row on the substrate, the metal bond diamond segment is in the shape of a cuboid, and the angle between the length direction of the cuboid and the length direction of the substrate is 90°. The preparation method of the metal bond diamond segment is as follows: 50% FeCu20 alloy powder, 12% copper powder, 15% iron powder, 11% ferrophosphorus powder, 4% cobalt powder and 4% manganese powder with a mass fraction were put into a three-dimensional mixer and mixed for 60 minutes, and then 4% diamond and metal diamond segment powder and 1.5% liquid paraffin were added, and metal bond diamond segments were obtained through hot pressing.

[0045] When grinding a workpiece, the metal bond diamond grinding block is welded to the clamping plate of the grinding disc.

[0046] Comparative Example 7 The ceramic-metal composite grinding block for rough grinding of microcrystalline glass in this comparative example is a conventional resin-bonded diamond grinding block for rough grinding of microcrystalline stone, such as Figure 5 As shown, the resin bonded diamond segment is the resin bonded diamond grinding block, which can be bonded to the cardboard by glue. The preparation method of the resin bonded diamond grinding block is as follows: 50% phenolic resin, 15% zinc oxide, 15% green silicon carbide powder and 5% sodium bicarbonate with a mass fraction are put into a three-dimensional mixer and mixed for 40 minutes, and then 15% diamond is added and mixed for another 60 minutes, then poured into a mold and pressed into shape using a hot press. The pressing and molding conditions are as follows: the hot press starts at a starting temperature of 100°C and a starting pressure of 10KN, gradually raises the temperature to 180°C, increases the pressure to 30KN, and keeps warm for 60 minutes. After completion, the burrs are removed, the size and shape are trimmed, and a resin-bonded diamond grinding block is obtained.

[0047] Comparative Example 8 The ceramic-metal composite grinding block used for rough grinding of microcrystalline glass in this comparative example is a conventional metal bond diamond grinding block, such as Figure 6 As shown, it includes an iron matrix and a metal binder diamond segment integrally formed with the iron matrix, and its preparation method is as follows: 50% copper powder, 10% iron powder, 11% ferrophosphorus powder, 6% cobalt powder, 4% manganese powder, 11% tin powder and 2% graphite powder with a mass fraction are put into a three-dimensional mixer and mixed for 60 minutes, and then 6% diamond and metal diamond segment powder and 1.5% liquid paraffin are added. After mixing for another 90 minutes, the mixed powder and iron matrix are put into a graphite mold, and the powder and the matrix are directly integrally formed by a hot press. The pressing molding conditions are as follows: the hot press starts at a starting temperature of 100°C and a starting pressure of 15KN, and then the temperature is gradually increased to 600°C, the pressure is increased to 40KN, and the temperature is kept for 6 minutes. After pressing and molding, the burrs are removed to obtain a metal bond diamond grinding block, and then the post-processing such as sharpening is performed.

[0048] 3. Experimental Examples The grinding blocks for rough grinding of glass-ceramics of Examples 1-3 and Comparative Examples 1-8 were tested and analyzed for sharpness, service life, and surface flatness after processing. The specific test steps are as follows: The test was carried out using a polishing machine. One polishing machine can be equipped with 18 grinding discs, and one grinding disc can be equipped with 6 grinding blocks; the grinding disc power is 15kw and the motor speed is 1460 rpm.

[0049] 1) Sharpness: It is reflected by the depth of processing microcrystalline glass plate. The specific implementation method is as follows: install a test grinding block in the polishing machine, test the thickness of the plate before the microcrystalline glass enters the polishing machine (such as 20mm), and test the thickness of the plate after processing in the polishing machine (such as 15mm). The difference between the two can be used to obtain the processing depth (such as the calculated processing depth is 20mm-15mm=5mm), which reflects the sharpness of the grinding block. The greater the processing depth, the better the sharpness.

[0050] 2) Service life: For glass-ceramics with dimensions of 2000mm long, 1600mm wide and 20mm thick, it is calculated based on the number of square meters processed by the test grinding block.

[0051] 3) Processing surface flatness: The microcrystalline glass plate is thrown out from a polishing machine equipped with a test abrasive block to see whether there are obvious scratches on the plate surface, whether the plate surface effect is uniform, and whether there is any missing polishing.

[0052] Embodiment and comparative example (composite grinding block adopts Figure 1 The test results of sharpness, service life and surface flatness after processing of the cutting edges (arrangement method) are shown in Table 3.

[0053] Table 3 Grinding performance test results of embodiments and comparative examples Group Processing depth (mm) Service life (square) Processing flatness Example 1 5-6 1.2-1.4 Smooth without missing Example 2 6-8 1.2-1.4 Smooth without missing Example 3 5-7 1.1-1.2 Smooth without missing Comparative Example 1 3-4 1.1-1.2 There are scratches and the board surface is black Comparative Example 2 3-4 1.1-1.2 There are scratches and the board surface is black Comparative Example 3 4-5 1.2-1.3 Scratches Comparative Example 4 4-5 1.2-1.3 Scratches Comparative Example 5 4-5 1.2-1.3 Scratches Comparative Example 6 3-4 1.2-1.3 Scratches Comparative Example 7 3-4 1.1-1.2 There is leakage Comparative Example 8 3-4 1.2-1.3 Scratches It can be seen from Table 3 that the ceramic-metal composite grinding block provided by the present invention can achieve a processing depth of more than 5 mm when rough-grinding microcrystalline glass, reflecting the high sharpness of the grinding block. At the same time, the service life can reach more than 1.1 cubic meters, maintaining a high service life. After rough grinding, the surface of the microcrystalline glass plate is smooth without missing any polishing, ensuring the surface quality of the microcrystalline glass plate and meeting the process requirements of the microcrystalline glass.

[0054] Compared with Example 2, if no graphite powder is added to the metal diamond segment (Comparative Example 1) and no pore-forming agent is added to the ceramic diamond segment (Comparative Example 2), the working layer will have poor heat dissipation, which will easily burn the surface of the microcrystalline glass. After rough grinding, the microcrystalline glass plate will have scratches and the plate surface will be blackened, and its sharpness and service life will also be reduced; if no copper powder is added to the metal diamond segment (Comparative Example 3), the working layer will have high hardness, poor heat dissipation, and will easily scratch the surface of the microcrystalline glass; if green silicon carbide is replaced with black silicon carbide in the ceramic diamond segment (Comparative Example 4), the sharpness will be poor, the processing depth will be insufficient, and the surface of the microcrystalline glass will be scratched; if iron-copper 10 alloy powder is used in the metal diamond segment (Comparative Example 5), the working layer will have high hardness, which will easily scratch the surface of the microcrystalline glass.

[0055] The conventional metal bond diamond grinding block (Comparative Example 6) has high hardness, poor heat dissipation, poor self-sharpening, and is easy to damage the surface of the microcrystalline glass, and causes the sharpness to deteriorate; the conventional resin bond diamond grinding block (Comparative Example 7) has low porosity, poor sharpness, insufficient processing depth, and missed polishing; the conventional metal bond diamond grinding block (Comparative Example 8) has low porosity, poor sharpness, insufficient processing depth, and is easy to cause scratches on the microcrystalline glass plate surface.

[0056] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ceramic-metal composite grinding block for rough grinding of microcrystalline glass, characterized in that: The invention comprises a substrate, wherein a plurality of ceramic diamond segments and a plurality of metal diamond segments are arranged on the substrate, and the grinding area ratio of all the ceramic diamond segments to all the metal diamond segments is (1-2.5):1; the ceramic diamond segments are made of 30-50% by mass of a ceramic binder, 20-30% by mass of diamond, 10-30% by mass of a pore-forming agent, 10-30% by mass of a green silicon carbide powder, and 2-5% by mass of a wetting agent; the metal diamond segments are made of 30-60% by mass of a FeCu20-50 alloy powder, 10-35% by mass of a copper powder, 10-30% by mass of an iron powder, 2-15% by mass of a phosphorus iron powder, 2-5% by mass of a cobalt powder, 2-5% by mass of a manganese powder, 3-10% by mass of a graphite powder, and 2-5% by mass of a diamond; A plurality of ceramic diamond segments and a plurality of metal diamond segments are arranged in a plurality of rows in the length direction of the substrate, and the ceramic diamond segment rows and the metal diamond segment rows are arranged alternately in the length direction of the substrate.

2. The ceramic-metal composite grinding block for rough grinding of glass-ceramics according to claim 1, characterized in that: The ceramic diamond segment is in the shape of a cylinder, and the metal diamond segment is in the shape of a cuboid; the angle between the length direction of the cuboid and the length direction of the substrate is 0° to 45°.

3. The ceramic-metal composite grinding block for rough grinding of glass-ceramics according to claim 1 or 2, characterized in that: The metal diamond segment is made of 30-35% FeCu20-50 alloy powder, 30-35% copper powder, 10-15% iron powder, 5-7% ferrophosphorus powder, 2-3% cobalt powder, 2-2.5% manganese powder, 4.5-5% graphite powder and 4-4.5% diamond in mass fraction.

4. The ceramic-metal composite grinding block for rough grinding of glass-ceramics according to claim 1, characterized in that: The method for manufacturing the metal diamond segment is to mix various raw materials and then press them into shape.

5. The ceramic-metal composite grinding block for rough grinding of microcrystalline glass according to claim 4, characterized in that: The pressing molding is hot pressing molding, the temperature of the hot pressing molding is 600-700°C, the time of the hot pressing molding is 3-10min, and the pressure of the hot pressing molding is 50-60KN.

6. The ceramic-metal composite grinding block for rough grinding of glass-ceramics according to claim 1, characterized in that: The ceramic diamond segment is manufactured by mixing various raw materials, then molding and sintering.

7. The ceramic-metal composite grinding block for rough grinding of microcrystalline glass according to claim 1, characterized in that: The preparation method of the ceramic binder comprises the following steps: mixing 30-60% by mass of silicon dioxide, 10-30% by mass of aluminum oxide, 10-30% by mass of boric acid, 5-15% by mass of zinc oxide, 5-15% by mass of lithium carbonate and 5-20% by mass of calcium carbonate, and then smelting, water quenching and crushing.

8. The ceramic-metal composite grinding block for rough grinding of microcrystalline glass according to claim 6, characterized in that: The sintering is performed by heating the temperature in stages from 30-50°C to 700-800°C and then keeping the temperature for 100-150 minutes.

9. The ceramic-metal composite grinding block for rough grinding of microcrystalline glass according to claim 8, characterized in that: The stepwise heating is as follows: heating from 30-50°C to 100-150°C at a heating rate of 1-1.5°C / min, keeping the temperature at 100-150°C for 80-100min, heating from 100-150°C to 400-450°C at a heating rate of 2.5-3°C / min, keeping the temperature at 400-450°C for 180-200min, and heating from 400-450°C to 700-800°C at a heating rate of 0.5-1°C / min.

10. The ceramic-metal composite grinding block for rough grinding of glass-ceramics according to claim 7, characterized in that: The smelting temperature is 1200-1400°C, and the smelting time is 100-200 min.